The First amendment in the Trump era - Zick, Timothy (New York, NY : Oxford University Press, 2019)
This text catalogues and examines the various First Amendment free speech and press controversies that have roiled the Trump presidency. It highlights both what is unique about those controversies, and what is consistent with historical patterns. From past conflicts and eras, the work draws various First Amendment lessons that will help guide readers through the Trump era.
Also issued in print: 2019.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on September 16, 2019).
Keywords: Freedom of expression -- United States; United States -- Politics and government -- 2017-